The Western literary canon in context. [Parts 1, 2 & 3] - Bowers, John M., 1949-; Teaching Company (Chantilly, VA : Teaching Co., 2008)
Professor John M. Bowers discusses why some works and not others become part of the literary canon. He examines the context of the works, and how academic curriculum perpetuates and changes the development of the canon.
Disc 5. Lecture 25. Nationalism and culture in Goethe's Faust -- Lecture 26. Melville's Moby-Dick and global literature -- Lecture 27. Cult classic: The charterhouse of Parma -- Lecture 28. East meets West in War and peace -- Lecture 29. Joyce's Ulysses and the avant-garde -- Lecture 30. The magic mountain and modern institutions -- Disc 6. Lecture 31. Mrs. Dalloway and post-war England -- Lecture 32. T.S. Eliot's divine comedy -- Lecture 33. Faulkner and the great American novel -- Lecture 34. Willa Cather and mosaics of identity -- Lecture 35. Tolkien's Lord of the Rings: literature? -- Lecture 36. Postcolonialism: the empire writes back.
"Literature & English language."
DVD.
Lecturer, John M. Bowers, University of Nevada, Las Vegas.
Thirty-six lectures (30 min. each).
Includes bibliographical references in accompanying guidebook.
Keywords: Canon (Literature); Literature -- History and criticism